Pengaruh Social Media Influencer dan Brand Awareness Terhadap Keputusan Pembelian Reddog Summarecon Mall Bekasi - Ainaya Ulfa; Mariah (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to know and analyze the effect of social media influencers and brand awareness on purchasing decisions of Reddog Summarecon Mall Bekasi. This study discusses the dimensions in the research variabels that are examined to determine the effect between variabels and objects. This study used quantitative methods through questionnaire survey distributed to 125 respondents who were processed using spss version 26 with nonprobability sampling method. hypotheses (t-test) results, social media influencer has significant effect on purchasing decisions. Brand Awareness has significant effect on purchasing decisions.